Kapasitas Kelembagaan Dalam Pembinaan Usaha Mikro Kecil Dan Menengah Di Kota Surakarta - Johan Bhimo Sukoco (Universitas Diponegoro, 2019)
Micro-, Small-, and Medium-Scale Enterprises (SMEs) building is often due to the weak institutional capacity. Limited capital ownership, poor business knowledge, and narrow business network make SME performers less powerful in improving their business. This research studied the SMEs building in Surakarta City, viewed from indicator of empowerment according to Mardikanto (2013), Institutional Building. This research employed a descriptive qualitative method. Data collection was carried out using interview, observation, and document analysis. Technique of analyzing data used was purposive sampling, data validation was carried out using method triangulation, and data analysis was conducted using an interactive model of analysis. The result of research showed that institutional capacity of SMEs in Surakarta City was still weak. SMEs performers (actors) still understood poorly the procedure and requirement of business licensing. This made them dealing with business licensing reluctantly, leading to the weak business institution. Pembinaan Usaha Mikro Kecil dan Menengah (UMKM) seringkali dikarenakan lemahnya kapasitas kelembagaan. Kepemilikan modal yang minim, pengetahuan usaha yang rendah, serta kurang luasnya jejaring usaha membuat pelaku UMKM menjadi kurang berdaya dalam meningkatkan usahanya. Penelitian ini mengkaji pembinaan UMKM di Kota Surakarta dilihat dari indikator pemberdayaan menurut Mardikanto (2010), yaitu Bina Kelembagaan. Penelitian ini menggunakan metode deskriptif kualitatif. Pengumpulan data menggunakan wawancara, observasi, dan analisis dokumen. Teknik pengumpulan data menggunakan purposive sampling, validitas data menggunakan triangulasi metode, dan analisis data menggunakan analisis interaktif. Hasil penelitian menunjukkan kapasitas kelembagaan UMKM di Kota Surakarta masih lemah. Pelaku UMKM masih kurang memahami prosedur dan persyaratan perizinan usaha. Hal ini mengakibatkan pelaku UMKM enggan melakukan pengurusan perizinan usaha yang berakibat lemahnya kelembagaan usaha.